Partisipasi Masyarakat Kabupaten Gayo Lues Terhadap Pemanfaatan Kawasan Penyangga (Buffer Zone) Taman Nasional Gunung Leuser - Meilinda Suriani Harefa; Gunmas Gunmas (Universitas Negeri Medan, 2011)
The aim of this research is to know the understanding of society about the benefit of buffer zone around in Gunung Leuser National Park (GLNP), to know the effort which are done by around of society as living earning and to know the participation of society to manage the buffer zone and also to see the relationship of socio economic to the participation of society. The research is done by the set of questioners and field observation. Society data is obtained at 4 regional districts of research in Sub-Province Gayo Lues to understand that their settlement resides at conservation frontier area and reside at GLNP buffer zone. Most of the people work as a farmer and carry out the cultivation of the plant in benefit the land as the first of their living earning to fulfill their life needed. The participation of society at Sub-Province Gayo Lues based on the result of calculation of questioners of expressed which have high percentage average. From calculation analyze correlation at 4 districts (Blangkejeren District, Kuta Panjang District, Blang Pegayon District and Puteri Betung District) represented Sub-Province Gayo Lues, it was obtained by the result that average didn’t have a significant relationship between socio economic variable to the participation of society.Keywords: Participation society, Gunung Leuser National Park, Sub-Province Gayo Lues, buffer zone